Blandstad - Phersson, Tobias (2010)
Throughout the history, the theories which have shaped our cities have varied from time to time. We have gone from a city development characterized by spontaneousness, where commerce and people side by side shared the space, into a function-based planning where people and functions are being increasingly separated. Regardless the forms of planning the city design causes implications for those who live there when the physical environment controls were we live, work and meet.